2007
DOI: 10.1242/jcs.03431
|View full text |Cite
|
Sign up to set email alerts
|

HDAC6 deacetylation of tubulin modulates dynamics of cellular adhesions

Abstract: Genetic or pharmacological alteration of the activity of the histone deacetylase 6 (HDAC6) induces a parallel alteration in cell migration. Using tubacin to block deacetylation of α-tubulin, and not other HDAC6 substrates, yielded a motility reduction equivalent to agents that block all NAD-independent HDACs. Accordingly, we investigated how the failure to deacetylate tubulin contributes to decreased motility in HDAC6-inhibited cells. Testing the hypothesis that motility is reduced because cellular adhesion is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
217
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(232 citation statements)
references
References 79 publications
(106 reference statements)
13
217
1
1
Order By: Relevance
“…Post-translational modifications of tubulin such as acetylation accumulate in stable microtubules 31 , however, it is unresolved as to whether acetylation actively stabilizes microtubules 30,[32][33][34][35][36] . As a measure of microtubule stability, we investigated their resistance to nocodazole, a microtubule depolymerizing drug.…”
Section: Resultsmentioning
confidence: 99%
“…Post-translational modifications of tubulin such as acetylation accumulate in stable microtubules 31 , however, it is unresolved as to whether acetylation actively stabilizes microtubules 30,[32][33][34][35][36] . As a measure of microtubule stability, we investigated their resistance to nocodazole, a microtubule depolymerizing drug.…”
Section: Resultsmentioning
confidence: 99%
“…Values are the average Ϯ SEM of at least 3 independent experiments; * P Ͻ 0.03; † P Ͻ 0.0001. peared independent of microtubule stability, 16,20,21 whereas in other studies including this one, increased acetylation induced increased microtubule stability. [13][14][15] The reasons for these conflicting results are not known but may reflect cell type differences in microtubule dynamics. Also, different assays were used to determine stability that likely vary in sensitivity and approach (for example, measuring nocodazole resistance versus real-time tubulin dynamics) such that conflicting results were obtained.…”
Section: Discussionmentioning
confidence: 99%
“…HDAC6 is the major tubulin deacetylase in liver and WIF-B cells (Grozinger et al 12 and manuscript in preparation), and when inhibited with TSA, increased microtubule acetylation and stability is observed. [13][14][15] We determined that 50 nM TSA for 30 minutes induced microtubule acetylation and stability to the same extent in WIF-B cells as did ethanol, allowing us to test our hypothesis. This result also suggested that acetylation induced microtubule stability, a topic that is currently controversial (for example, see Tran et al 15 and Palazzo et al 16 and the Discussion section).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…13,14 Hyperacetylated microtubules decreased microtubule dynamics, increased microtubule stability and decreased cell migration. 15 Therefore, tubulin acetylation/deacetylation is implicated in the control of microtubule function and, therefore, the regulatory mechanism of tubulin acetylation/deacetylation by acetylase/deacetylase has attracted much attention.…”
Section: Sirt2 and Endothelial Microtubule Reorganization A Hashimotomentioning
confidence: 99%